Plant-based ground beef alternatives in comparison to ground beef of various fat percentages - Davis, Samuel Garret (Kansas State University, 2021)
The objective of this study was to determine of current plant-based protein ground beef alternatives (GBA) offer similar subjective and objective characteristics to ground beef (GB) patties of varying fat percentages. Fifteen different production lots (n = 15 / fat level) of 1.36 kg GB chubs of three different fat levels (10%, 20%, and 30%) were collected from retail markets in the Manhattan, KS area. Additionally, GBA products including a soy and potato-protein based Foodservice GBA (FGBA), a pea-protein based Retail GBA (RGBA), and a Traditional soy- protein based GBA (TGBA), (n = 15 production lots / product) currently available through commercial channels were collected from retail markets and a commercial foodservice chain. All GB and GBA treatments were formed into 151-g patties and frozen at -40°C. Patties were thawed 12-24 h prior to cooking and were cooked to 71°C, cut into six equally sized wedges, and served to consumers. Consumers (n = 120) were fed six samples in a random order and evaluated sample appearance, juiciness, tenderness, overall flavor liking, beef flavor liking, texture liking, and overall liking. Additionally, the following assays were conducted: color analysis, texture profile analysis (TPA), shear force (SF), pressed juice percentage (PJP), fat percentage, and moisture percentage. Patties used for TPA and SF were cooked to 71°C and cores were taken from each patty for TPA and two strips taken from each patty for SF. Patties were evaluated for L*, a*, and b* both in the raw, precooked state as well as after cooking for both external and internal color. Pressed juice percentage measured the percentage of weight lost from cooked samples. During cooking for TPA, SF, and PJP, patty weights, diameters and thicknesses were measured for determination of size change through cooking. All three GB samples rated higher (P < 0.05) than the three GBA samples for appearance, overall flavor, beef flavor, and overall liking. Retail GBA rated lowest (P < 0.05) for appearance, overall flavor, texture, and overall liking. Of the GBA samples, FGBA rated highest (P < 0.05) for juiciness, beef flavor, and texture liking, and TGBA rated lowest (P < 0.05) for juiciness. Moreover, of the GBA samples, FGBA and TGBA rated similar (P > 0.05) for appearance, tenderness, overall flavor liking, and overall liking. Among the GB samples, no differences (P > 0.05) were found for appearance, juiciness, overall flavor liking, beef flavor liking, or overall liking. When evaluating raw color, TGBA had the highest (P < 0.05) a* value and were redder when compared to all other treatments. Traditional GBA and RGBA had the highest (P < 0.05) a* value, while FGBA, and 30% and 10% fat GB had the lowest (P < 0.05) a* value for cooked surface color. Additionally, 30% and 20% fat GB had higher (P < 0.05) L* values for internal cooked color than all other treatments, with all GBA patties having the lowest (P < 0.05) L* values. For texture attributes, RGBA and FGBA had lower (P < 0.05) values for cohesiveness, gumminess, hardness, and chewiness. For SF, the three GBA were more tender (P < 0.05) than all three GB treatments, with FGBA and RGBA being more tender (P < 0.05) than all treatments. The three GB treatments had greater (P < 0.05) PJP values than all GBA, indicating the GB was juicier than any of the GBA evaluated. Finally, during cooking, the three GB treatments had a greater (P < 0.05) cook loss percentage and decrease in patty diameter and thickness than the three GBA, with FGBA and RGBA increasing in thickness during cooking. This clearly indicates the eating experience provided by the GBA is different than that provided by traditional GB. Thus, consumers who purchase GBA should not expect the same eating quality as they would receive with GB.
Keywords: Alternative proteins; Consumer; Ground beef; Ground beef alternative; Palatability